Chitosan/Poly(ε-caprolactone) blend scaffolds for cartilage repair - Neves, Sara Carvalheira (2011)
Chitosan (CHT)/poly(ε-caprolactone) (PCL) blend 3D fiber-mesh scaffolds were studied as possible support structures for articular cartilage tissue (ACT) repair. Micro-fibers were obtained by wet-spinning of three different polymeric solutions: 100:0 (100CHT), 75:25 (75CHT) and 50:50 (50CHT) wt.% CHT/PCL, using a common solvent solution of 100 vol.% of formic acid. Scanning electron microscopy (SEM) analysis showed a homogeneous surface distribution of PCL. PCL was well dispersed throughout the CHT phase as analyzed by differential scanning calorimetry and Fourier transform infrared spectroscopy. The fibers were folded into cylindrical moulds and underwent a thermal treatment to obtain the scaffolds. μCT analysis revealed an adequate porosity, pore size and interconnectivity for tissue engineering applications. The PCL component led to a higher fiber surface roughness, decreased the scaffolds swelling ratio and increased their compressive mechanical properties. Biological assays were performed after culturing bovine articular chondrocytes up to 21 days. SEM analysis, live-dead and metabolic activity assays showed that cells attached, proliferated, and were metabolically active over all scaffolds formulations. Cartilaginous extracellular matrix (ECM) formation was observed in all formulations. The 75CHT scaffolds supported the most neo-cartilage formation, as demonstrated by an increase in glycosaminoglycan production. In contrast to 100CHT scaffolds, ECM was homogenously deposited on the 75CHT and 50CHT scaffolds. Although mechanical properties of the 50CHT scaffold were better, the 75CHT scaffold facilitated better neo-cartilage formation.